Local Government Integrity and Human Resource Competence in Enhancing Financial Reporting Quality: A Systematic Literature Review - Faby Saktioriza Nugraha; Saring Suhendro; Chara Pratami Tidespania Tubarad (Jurnal Ekonomi Manajemen Bisnis dan Akuntansi, 2026)
The objective of this study is to comprehensively review the literature discussing the synergistic relationship between local government apparatus integrity and human resource (HR) competence on the quality of Local Government Financial Reports (LKPD). Integrity serves as a pillar of good governance, while HR competence constitutes the technical prerequisite for preparing financial reports in accordance with Government Accounting Standards (SAP). The method employed is a Systematic Literature Review (SLR) of reputable journals published in the last five years (2021-2025). The results indicate that integrity mediates and strengthens the influence of competence and budget quality on financial report reliability. This article offers theoretical implications regarding the importance of strengthening a culture of integrity alongside enhancing accounting competence for officials preparing the LKPD.